Interdependent recruitment of SAGA and Srb mediator by transcriptional activator Gcn4p - Hongfang Qiu (2018)
Transcriptional activation by Gcn4p is enhanced by the coactivators SWI/SNF, SAGA, and Srb mediator, which stimulate recruitment of TATA binding protein (TBP) and polymerase II to target promoters. We show that wild-type recruitment of SAGA by Gcn4p is dependent on mediator but independent of SWI/SNF function at three different promoters. Recruitment of mediator is also independent of SWI/SNF but is enhanced by SAGA at a subset of Gcn4p target genes. Recruitment of all three coactivators to ARG1 is independent of the TATA element and preinitiation complex formation, whereas efficient recruitment of the general transcription factors requires the TATA box. We propose an activation pathway involving interdependent recruitment of SAGA and Srb mediator to the upstream activation sequence, enabling SWI/SNF recruitment and the binding of TBP and other general factors to the promoter. We also found that high-level recruitment of Tra1p and other SAGA subunits is independent of the Ada2p/Ada3p/Gcn5p histone acetyltransferase module but requires Spt3p in addition to subunits required for SAGA integrity. Thus, while Tra1p can bind directly to Gcn4p in vitro, it requires other SAGA subunits for efficient recruitment in vivo.